Corporate Social Responsibility Considered With Two Systems Theories: A Case from Serbia - Zlatanović, Dejana; Mulej, Matjaž; Ženko, Zdenka (Naše gospodarstvo/Our economy, 2022)
Corporate Social Responsibility (CSR) becomes one of the prerequisites for success of contemporary organizations aimed at humankind’s survival by sustainable development. As SR behavior can generate significant benefits, more and more organizations are developing SR strategic plans and implementing SR initiatives. In ISO 26000, CSR has three basic concepts: Responsibility for one's influences over society, interdependence and holistic approach. Therefore, authors focus on systemic approach to CSR. The purpose is to demonstrate how combined use of appropriate systems theories can help dealing with CSR. Accordingly, Dialectical Systems Theory (DST) and System Dynamics (SD), as relevant systems theories, i.e. methodologies stemming from different systemic paradigms, were selected. DST helped to identify some relevant aspects and components of CSR which were empirically tested in businesses in the Republic of Serbia. Hence, the following factors, i.e. groups of SR activities are selected as relevant for improving organizational performance: General CSR activities; CSR activities towards consumers; CSR activities towards environmental protection and beneficiaries’ health, and Socially responsible after sales activities. In addition, empirical research results indicating the influence of the above factors on performance were the basis for using the tools of SD, such as stock and flow diagrams and causal loop diagrams. SD tools contribute to simulating the system's future behavior, i.e. future performance level after improving these CSR activities. Authors introduce a new, systemic approach to conceptualizing and researching CSR by providing appropriate methodological support for exploring relevant interdependencies of CSR aspects.